Focused ultrasound for the remote modulation of nitric oxide release from injectable PEG-fibrinogen hydrogels for tendon repair - Meyers, Kaylee M.; Simon, Alex; Khan, Zerin M.; Rajachar, Rupak M.; Vlaisavljevich, Eli (Frontiers in Materials, 2023)
Tendon disorders such as tendinosis, the degradation of collagen in tendon, or tendonitis, inflammation of tendon tissue, contribute to 30% of musculoskeletal complaints. To address the limitations of currently available treatments for tendon repair, an injectable polyethylene glycol (PEG)-fibrinogen hydrogel encompassing nitric oxide (NO) releasing µ-particles was generated. The release of NO, a therapeutic molecule that modulates many wound healing processes, from the hydrogel can be modified with thermal and mechanical stimulus. To achieve remote control over NO release from hydrogels after deployment, focused ultrasound (FUS) was explored as it provides highly controlled thermal and mechanical stimulus non-invasively. In this work, the ability of FUS to remotely elicit on-demand NO generation from acoustically active composite hydrogels via thermal and/or mechanical stimulus was explored. Specifically, the temperature and time-dependent release of NO was simulated and characterized when applying FUS to composite hydrogels. Results from acoustic simulations as well as thermocouple heating studies indicated that high spatial and temporal control over hydrogel warming could be achieved non-invasively with a 3.5MHz FUS transducer. FUS was also able to remotely control NO release from hydrogels with various thermal magnitudes and durations. Additionally, no apparent changes in the mechanical properties of hydrogels were observed with FUS treatment. Utilizing FUS thermal and mechanical stimulus provides a potential method of remotely controlling NO release from hydrogels at a wound site to aid in tendon repair.